KNOWLEDGE MANAGEMENT IN IT-PROJECTS - Колесникова, Екатерина Викторовна; Негри, Артем Александрович (Eastern-European Journal of Enterprise Technologies, 2013)
With the continuous technical and economic growth of businesses and global competition winning organization, managed to introduce new information technologies that contribute to significant changes in the field of science and technology. Innovations are implemented in the form of large interdisciplinary projects. It is to such projects and IT-related projects, and in particular web-projects. The main cause of failure of most software projects is the use of inadequate management of the design and not the correct approach in the interaction of all the participants. The classical methods of control do not work in cases where the structure and properties of the managed object is not known and / or change over time. These approaches also will not help if the current properties of the object do not allow it to move with the desired characteristics, ie if the working group of the project can not provide the required efficiency. Proper formation of the team, good distribution of resources, time and employment - these are the main features of the project manager. Creating an environment in which team members will be highly motivated to get satisfaction from their professional activities, to participate in working with each other will help you project is within the basic constraints of project management - project completion on time, within budget and in accordance with specifications.